SASTRA ‘MUNGKIN’: KONTESTASI SIMBOLIK ANDREA HIRATA DALAM ARENA SASTRA INDONESIA - Kukuh Yudha Karnanta (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
The article entitled Sastra ‘Mungkin’: A Symbolic contestation of Andrea Hirata in Indonesian Literature Arena is discussing the literary practices of Andrea Hirata, a novelist who surprisingly popular in Indonesian literature from 2006 to present. This article aims to explicit the views and contestation of Andrea Hirata literary practices based on his views in gaining legitimacy of his works as an author. This research applies Pierre Bourdieu’s Arena Cultural Production, which assumes that literature is not just a question of aesthetics but also the struggle of positions between agents operating in the literary arena. According to the research that has been conducted, the result reveals that Andrea Hirata actually has a tendency, furthermore, obsession, in order to gain a specific legitimacy as an author (literar y figure). In doing so, Andrea Hirata impose his views about possibility in Indonesian literature.Keywords: field, Andrea Hirata, symbolic violence, legitimacy, doxa, heterodoxa